2016
DOI: 10.3389/fsurg.2016.00066
|View full text |Cite
|
Sign up to set email alerts
|

3D Volumetric Modeling and Microvascular Reconstruction of Irradiated Lumbosacral Defects after Oncologic Resection

Abstract: BackgroundLocoregional flaps are sufficient in most sacral reconstructions. However, large sacral defects due to malignancy necessitate a different reconstructive approach, with local flaps compromised by radiation and regional flaps inadequate for broad surface areas or substantial volume obliteration. In this report, we present our experience using free muscle transfer for volumetric reconstruction, in such cases, and demonstrate three-dimensional (3D) haptic models of the sacral defect to aid preoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…We also recently demonstrated the utility of a 3D-printed biomodel for planning perforator flap reconstruction of a sacral wound defect post-oncologic resection ( 117 ). Likewise, we used Osirix to translate the preoperative sacral CTA data into a CAD file.…”
Section: D Printing In Plastic and Reconstructive Surgerymentioning
confidence: 99%
“…We also recently demonstrated the utility of a 3D-printed biomodel for planning perforator flap reconstruction of a sacral wound defect post-oncologic resection ( 117 ). Likewise, we used Osirix to translate the preoperative sacral CTA data into a CAD file.…”
Section: D Printing In Plastic and Reconstructive Surgerymentioning
confidence: 99%
“…An increasing number of studies use MRI for preoperative planning in plastic surgery, such as a study that identified the location of perforated vessels in a PI using MRI 37 and a study of 3D printed haptic analysis of a lumbosacral defect using MRI 38 …”
Section: Discussionmentioning
confidence: 99%
“…Gillis and Morris [2] described the first use of 3D printing to produce perforator vascular anatomy in surgical planning in 2014. Since then, several other authors have described their experience with 3D printed models in complex reconstruction [14][15][16][17].…”
Section: Fig 4 3d Printed Model For Breast Reconstructionmentioning
confidence: 99%